FOREGNISASI SEBAGAI IDEOLOGI TERJEMAHAN LAGU BAHASA JAWA VERSI INDONESIA: KAJIAN ANALISA TERJEMAHAN - Ika Susanti (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The highest of indonesian musician to develop Indonesia’s song force them to recycle a popular song into two version (Javanese and indonesia). This paper focused in analysing how the process of transalation is and what ideology that was used in transalting these songs. Qualitative is the method that was used in this research. The data of this research is dangdut songs entitile “layang sworo” and ”oplosan”. In gathering the data, researcher used observation and questioner and in analyzing the data researcher used analysing and clasifiying. The result of the analsis shows that the translator used foreignisation ideology in translating these songs. It goes to that conclusion because the characteristic and the use of method in translating the songs. The characteristics are the translator put some word in source language in the target language, the target language text is like a translation text, and the translator almost did not add or reduce the source language text in the target language text. Then the methods were used are word for word, literal translation and semantic translation.